Towards Sustainable Marketing: Strategy in Slovak Companies - Juraj Chebeň; Drahoslav Lančarič; Radovan Savov; Marián Tóth; Jan Tlučhoř (Amfiteatru Economic)
Despite the growing attention that is being paid to sustainability in the literature, little empirical research has been conducted on developing the link between sustainability and marketing strategy and moreover, only a few empirical studies have investigated this issue in Central and Eastern Europe. The conducted empirical survey examines the relationship between marketing strategy and sustainability from the perspective of enterprises in Slovakia. The authors have used binary logistic regression as an evaluation method. The empirical findings are based on 896 responses from different forms of companies in Slovak Republic. The results show that the legal form of a business organization is a relevant determinant of philosophy of sustainability when organization defines a marketing strategy and implements it into corporate strategy. Based on the results it can also be concluded that the environmental aspect of sustainability is determined by the size of organization and the sector of national economy where a company operates, while the social aspect is mainly determined by the share of foreign capital in the ownership structure of an organisation. This study contributes to the European research that studies the relation between sustainability and the marketing strategy by means of an empirical investigation in business organisations in a transition economy such as Slovakia.